Multilayer film, as well as laminate therewith, packaging bag and packaged product
Patent Information
- Application Number
- JP2024135704
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-15
- Filing Date
- 2024-08-15
- Publication Date
- 2025-02-28
AI Technical Summary
【0017】 本開示によれば、積層体に対して優れた製袋適性を付与でき、優れた視認性を有することが可能な多層フィルム、並びにこれを用いた積層体、包装袋及び包装製品が提供される。
Smart Images

Figure 2025028036000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a multilayer film, and a laminate, a packaging bag, and a packaging product using the same. [Background technology]
[0002] Packaging bags used for packaging food, medicine, etc. are generally obtained by making a laminate having a base layer and a sealant layer. One such laminate known is a laminate having a protective layer, a base layer, and a sealant layer in this order, in which the base layer and the sealant layer contain polyethylene, the protective layer contains a thermosetting resin or a resin with a melting point of 160°C or higher, and the proportion of polyethylene in the entire laminate is 90% by mass or more (see Patent Document 1 below), and it has been proposed that this laminate can be used to improve recyclability and heat sealability. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2022 / 230812 Summary of the Invention [Problem to be solved by the invention]
[0004] Incidentally, a laminate may have a printed layer provided between layers, and in such a case, high visibility of the printed layer is required at least in the base layer. However, the laminate described in Patent Document 1 may not provide sufficiently high visibility. Even if the laminate provides sufficiently high visibility, the laminate may not be suitable for bag making. That is, the laminate described in Patent Document 1 above has room for improvement in terms of simultaneously satisfying excellent suitability for bag making and excellent visibility.
[0005] The present disclosure has been made in consideration of the above-mentioned problems, and aims to provide a multilayer film that can impart excellent bag-making suitability to a laminate and has excellent visibility, as well as a laminate, a packaging bag, and a packaging product using the same. [Means for solving the problem]
[0006] In order to solve the above-mentioned problems, one aspect of the present disclosure provides a multilayer film comprising an outermost layer containing a thermoplastic resin and a polyethylene layer containing a polyethylene-based resin, wherein the thermoplastic resin has a melting point of 160°C or more, and the polyethylene layer includes a high elastic modulus layer having a composite elastic modulus of 1.4 GPa or more and less than 2.4 GPa as measured by a nanoindentation method in a cross section in the thickness direction of the polyethylene layer. The multilayer film described above can impart excellent suitability for bag making to the laminate, and can provide excellent visibility. The reason why the above-mentioned effect is obtained by the above-mentioned multilayer film is not clear, but is thought to be as follows. That is, when the composite elastic modulus of the high elastic modulus layer contained in the polyethylene layer is 1.4 GPa or more, the density of the polyethylene layer as a whole becomes high and the polyethylene layer becomes less likely to soften due to heat. Therefore, the shape of the polyethylene layer can be maintained during heat sealing, and shrinkage, distortion, and fluctuation in film thickness of the polyethylene layer can be suppressed. In addition, by making the melting point of the outermost layer 160°C or higher, the outermost layer itself is less likely to melt when the laminate is heat-sealed. In addition, since the outermost layer has a high melting point of 160°C or higher and is less likely to melt when heat-sealed, it is possible to prevent the outermost layer from sticking to the seal bar or from wrinkling. Therefore, it is believed that the multilayer film can impart excellent bag-making suitability to the laminate even if the heat-sealing temperature varies during heat-sealing. Furthermore, by having the composite elastic modulus of the high elastic modulus layer contained in the polyethylene layer be less than 2.4 GPa, the density of the high elastic modulus layer does not become too high, and the visibility of the multilayer film is less likely to decrease. As a result, it is believed that the multilayer film can have excellent visibility. From the above, it is believed that the above effects can be obtained by using the multilayer film. If the composite elastic modulus of the high elastic modulus layer contained in the polyethylene layer is less than 1.4 GPa, the film thickness of the portion pressed in during heat sealing will be small, making it more likely that defects in bag production will occur due to breakage, fusion, dents, etc.
[0007] In the above multilayer film, the ratio of the thickness of the high elastic modulus layer to the total thickness of the polyethylene layers is preferably 50% or more. In this case, the contribution of the high modulus layer to the entire polyethylene layer can be increased by increasing the thickness ratio of the high modulus layer, and therefore the multilayer film can impart superior bag-making suitability to the laminate.
[0008] In the above multilayer film, the ratio of the thickness of the outermost layer to the total thickness of the multilayer film is preferably 3% or more. In this case, the contribution of the outermost layer to the overall thickness of the multilayer film can be increased by increasing the ratio of the thickness of the outermost layer to the overall thickness of the multilayer film, and therefore the multilayer film tends to impart better bag-making suitability to the laminate. In the above multilayer film, it is preferable that the degree of crystallinity of the polyethylene layer is less than 35% as measured by a parallel beam method of X-ray diffraction within a diffraction angle range of 10° to 30°. When the crystallinity of the polyethylene layer is less than 35%, the portion of the polyethylene layer near the surface becomes less susceptible to peeling, and the adhesive strength between the polyethylene layer and the outermost layer or an adhesive layer formed on the polyethylene layer can be improved.
[0009] Another aspect of the present disclosure provides a laminate comprising a multilayer film and a sealant layer, the sealant layer containing a polyethylene-based resin, the multilayer film being composed of the multilayer film described above, and the polyethylene layer being disposed on the sealant layer side in the multilayer film. The laminate has excellent bag-making suitability and visibility.
[0010] In the above laminate, the mass proportion of the polyethylene resin in the entire laminate is preferably 90 mass % or more. In this case, the recyclability can be further improved.
[0011] The laminate may further comprise a first adhesive layer between the multilayer film and the sealant layer.
[0012] It is preferable that the laminate further comprises an intermediate layer and a second adhesive layer, in this order from the first adhesive layer side, between the first adhesive layer and the sealant layer, and that the intermediate layer contains a polyethylene-based resin. In this case, the mass proportion of the polyethylene resin in the entire laminate can be more easily increased.
[0013] It is preferable that the laminate further comprises a gas barrier layer between the multilayer film and the intermediate layer. In this case, the gas barrier property of the laminate can be further improved.
[0014] It is preferable that the laminate further includes a gas barrier layer between the intermediate layer and the sealant layer. In this case, the gas barrier property of the laminate can be further improved.
[0015] Yet another aspect of the present disclosure provides a packaging bag obtained by making the above-mentioned laminate into a bag. The packaging bag is obtained by making the above-mentioned laminate into a bag. Since the laminate has excellent suitability for bag making, it is possible for the laminate to have an excellent appearance and also excellent visibility.
[0016] Another aspect of the present disclosure provides a packaging product comprising the packaging bag described above and contents contained within the packaging bag. The packaging bag is obtained by making the above-mentioned laminate into a bag, and since the laminate has excellent bag-making suitability, it is possible for the laminate to have an excellent appearance and also excellent visibility, so that the packaged product also has an excellent appearance and the contents can be easily visually confirmed. Effect of the Invention
[0017] According to the present disclosure, there are provided a multilayer film that can impart excellent bag-making suitability to a laminate and provide excellent visibility, as well as a laminate, a packaging bag, and a packaging product using the same. [Brief description of the drawings]
[0018] [Figure 1] FIG. 1 is a cross-sectional view illustrating one embodiment of a multilayer film of the present disclosure. [Diagram 2] FIG. 1 is a cross-sectional view showing one embodiment of a laminate of the present disclosure. [Diagram 3] FIG. 1 is a cross-sectional view illustrating one embodiment of a packaging product of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] Hereinafter, embodiments of the present disclosure will be described in detail. However, the present disclosure is not limited to the following embodiments.
[0020] <Multilayer film> First, an embodiment of the multilayer film of the present disclosure will be described with reference to Fig. 1. Fig. 1 is a cross-sectional view showing one embodiment of the multilayer film of the present disclosure. The multilayer film 10 shown in FIG. 1 comprises an outermost layer 11 containing a thermoplastic resin and a polyethylene layer 12 containing a polyethylene-based resin. The thermoplastic resin of the outermost layer 11 has a melting point of 160°C or higher, and the polyethylene layer 12 includes a high elastic modulus layer having a composite elastic modulus of 1.4 GPa or more and less than 2.4 GPa as measured by nanoindentation in a cross section of the thickness direction of the polyethylene layer 12.
[0021] According to the multilayer film 10, a laminate including the multilayer film 10 and a sealant layer can be provided with excellent suitability for bag making, and can have excellent visibility.
[0022] The outermost layer 11 and the polyethylene layer 12 will be described in detail below.
[0023] (top layer) The outermost layer 11 is a layer containing a thermoplastic resin having a melting point of 160° C. or higher. Examples of the thermoplastic resin having a melting point of 160° C. or higher include polypropylene resin, polyester resin, polyamide resin, and polyethylene vinyl alcohol resin (EVOH). These may be used alone or in combination of two or more.
[0024] Examples of polypropylene resins include homopolypropylene and block polypropylene. Examples of polyester resins include polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polyethylene naphthalate (PEN), and polybutylene naphthalate (PBN). Examples of polyamide resins include nylon 6, nylon 6,6, a copolymer of nylon 6 and nylon 6,6, nylon 6, nylon 9T, nylon 10, polymetaxylylene adipamide (MXD6), nylon 11, and nylon 12. The thermoplastic resin only needs to have a melting point of 160°C or higher, and may be a mixture of a thermoplastic resin having a melting point below 160°C and a thermoplastic resin having a melting point of 160°C or higher. In addition, the melting point of a thermoplastic resin refers to the melting point of that resin when the thermoplastic resin is composed of one type of resin, and refers to the highest melting point among the multiple melting points when the thermoplastic resin is composed of a mixture of multiple types of resin and has multiple melting points.
[0025] The melting point of the thermoplastic resin may be equal to or higher than 160° C. When the melting point of the thermoplastic resin is equal to or higher than 160° C., excellent suitability for bag formation can be imparted to the laminate. The melting point of the thermoplastic resin is preferably 180° C. or higher, more preferably 200° C. or higher, and particularly preferably 220° C. or higher. The melting point of the thermoplastic resin may be 270°C or less, 260°C or less, or 240°C or less.
[0026] The outermost layer 11 may further contain additives such as a flame retardant, a slip agent, an antiblocking agent, an ultraviolet absorber, an antioxidant, a plasticizer, a light stabilizer, a lubricant, a tackifier, and an antistatic agent, as necessary.
[0027] The thickness of the outermost layer 11 is not particularly limited, and can be appropriately determined according to the cost and application, taking into consideration the suitability of the manufacturing method and device, and the suitability for lamination with other layers. From the viewpoint of imparting better suitability for bag making to the laminate, the thickness of the outermost layer 11 is preferably 0.7 μm or more, more preferably 1 μm or more, and particularly preferably 2 μm or more. From the viewpoint of further improving recyclability, the thickness of the outermost layer 11 is preferably 10 μm or less, more preferably 8 μm or less, and particularly preferably 6 μm or less.
[0028] The ratio R1 of the thickness of the outermost layer 11 to the overall thickness of the multilayer film 10 is not particularly limited, but is preferably 3% or more, and more preferably 5% or more. By increasing R1, the contribution of the outermost layer 11 can be increased. Therefore, the multilayer film 10 tends to impart better bag-making suitability to the laminate. From the viewpoint of further improving recyclability, R1 is preferably 30% or less, more preferably 20% or less, and particularly preferably 10% or less.
[0029] (Polyethylene layer) The polyethylene layer 12 includes a high elastic modulus layer having a composite elastic modulus of 1.4 GPa or more and less than 2.4 GPa as measured by nanoindentation in a cross section of the polyethylene layer 12 in the thickness direction. The composite elastic modulus of the high elastic modulus layer may be 1.4 GPa or more and less than 2.4 GPa, but is preferably 1.6 GPa or more, more preferably 1.8 GPa or more, and particularly preferably 2.0 GPa or more. The composite elastic modulus of the high elastic modulus layer may be 2.3 GPa or less, or 2.2 GPa or less. The composite elastic modulus of the high elastic modulus layer can be adjusted, for example, by using a single high density polyethylene resin or a plurality of types of high density polyethylene resin, stretching treatment, or the use of additives, without being limited to a particular means.
[0030] The polyethylene layer 12 is a high modulus layer having a composite modulus of elasticity of 1.4 GPa or more and less than 2.4 GPa, and may be a single layer or a laminate of multiple layers.
[0031] The polyethylene layer 12 may be composed of only a high elastic modulus layer having a composite elastic modulus of 1.4 GPa or more and less than 2.4 GPa, or may be composed of a laminate of a high elastic modulus layer having a composite elastic modulus of 1.4 GPa or more and less than 2.4 GPa and a low elastic modulus layer having a composite elastic modulus less than 1.4 GPa. Here, for example, the layer in contact with the outermost layer 11 may be either a low elastic modulus layer or a high elastic modulus layer. The polyethylene layer 12 may be constructed of a laminate of a high modulus layer having a composite modulus of 1.4 GPa or more and less than 2.4 GPa, and an ultra-high modulus layer having a composite modulus of 2.4 GPa or more.
[0032] The polyethylene layer 12 contains a polyethylene-based resin. Examples of the polyethylene-based resin include low-density polyethylene resin (LDPE), medium-density polyethylene resin (MDPE), high-density polyethylene (HDPE), linear low-density polyethylene resin (LLDPE), ethylene-vinyl acetate copolymer (EVA), ethylene-α-olefin copolymer, ethylene-(meth)acrylic acid copolymer, and polyethylene-based resin modified with an unsaturated carboxylic acid or a derivative thereof. These may be used alone or in combination of two or more. Examples of unsaturated carboxylic acids include acrylic acid, methacrylic acid, maleic acid, fumaric acid, crotonic acid, itaconic acid, citraconic acid, etc. Examples of derivatives of unsaturated carboxylic acids include methyl acrylate, methyl methacrylate, ethyl acrylate, propyl acrylate, butyl acrylate, butyl methacrylate, glycidyl acrylate, glycidyl methacrylate, vinyl acetate, acrylamide, methacrylamide, sodium acrylate, maleic anhydride, etc.
[0033] The polyethylene layer 12 may further contain a flame retardant, a slip agent, an antiblocking agent, an ultraviolet absorbing agent, an antioxidant, a plasticizer, a light stabilizer, a lubricant, a tackifier, and an antistatic agent, if necessary.
[0034] The polyethylene layer 12 may be a stretched film or a non-stretched film. The stretched film may be a uniaxially stretched film or a biaxially stretched film. The polyethylene layer 12 is preferably a non-stretched film from the viewpoint of improving adhesion to the outermost layer 11 and an adhesive layer formed on the polyethylene layer 12. Also, it is preferably a stretched film from the viewpoint of improving strength and transparency.
[0035] The crystallinity of the polyethylene layer 12 is not particularly limited, but is preferably less than 80%. The crystallinity of the polyethylene layer 12 is preferably 75% or less, and more preferably 70% or less. If the crystallinity is less than 80%, the portion near the surface of the polyethylene layer 12 becomes difficult to peel off, and sufficient adhesive strength is easily obtained between the polyethylene layer 12 and the outermost layer 11 or an adhesive layer formed on the polyethylene layer 12. The crystallinity can be adjusted by the density of the raw resin or the stretching treatment of the film before stretching. For example, the crystallinity can be increased by increasing the density of the raw resin or by uniaxially or biaxially stretching the film. Furthermore, the crystallinity increases as the stretching ratio increases. For example, the crystallinity of the polyethylene layer 12 is preferably within a range of 10% or more and less than 80%. From the viewpoint of improving the adhesive strength between the polyethylene layer 12 and the outermost layer 11 or between the polyethylene layer 12 and an adhesive layer formed thereon, it is effective to reduce the crystallinity, which is more preferably less than 35%, and even more preferably 30% or less. On the other hand, from the viewpoint of improving the strength and transparency of the polyethylene layer 12, it is effective to increase the crystallinity, which is preferably 35% or more, and more preferably 45% or more.
[0036] Here, the crystallinity is determined by an X-ray diffraction method using a parallel beam method. Specifically, the crystallinity is determined as follows. First, the XRD pattern of the film is obtained by out-of-plane measurement using a wide-angle X-ray diffractometer manufactured by Rigaku Corporation, scanning the diffraction angle range of 10° to 30° with 2θ / θ. The characteristic X-ray CuKα is used as the X-ray, which is collimated by a multilayer mirror and incident on the surface of the film, and the diffracted X-ray is detected by a scintillation detector equipped with a flat collimator. At this time, the X-ray is incident from the polyethylene layer 12 side of the multilayer film 10. From the obtained XRD pattern, the peak area A1 of the crystalline component and the halo pattern area A2 of the amorphous component are calculated, and the ratio of the peak area (A1) of the crystalline component to the sum of these areas (=A1+A2) as the reference (100%) is calculated as the crystallinity (%) of the film. Specifically, the crystallinity is calculated based on the following formula: Crystallinity (%) = 100 x A1 / (A1+A2) In the case of polyethylene, when scanning is performed at a diffraction angle range of 10° to 30°, two sharp crystalline component peaks corresponding to the (110) and (200) planes and a broad amorphous component halo pattern are observed. These are separated and analyzed to calculate the area of the crystalline component peak (A1) and the area of the amorphous component halo pattern (A2).
[0037] The melting point of the polyethylene layer 12 is not particularly limited, but is preferably less than 160° C. Here, the melting point of the polyethylene layer 12 refers to the highest melting point in the temperature range in which the melting point of the polyethylene resin can be observed when measuring the melting point of the multilayer film 10. The melting point of the polyethylene layer 12 may be 140° C. or less, 137° C. or less, or 135° C. or less. The melting point of the polyethylene layer 12 may be 125° C. or more, 129° C. or more, or 130° C. or more.
[0038] The thickness of the polyethylene layer 12 is not particularly limited, and can be appropriately determined according to the cost and application, taking into consideration the suitability of the manufacturing method and equipment, and the suitability for lamination with other layers. From the viewpoint of imparting better suitability for bag formation to the laminate, the thickness of the polyethylene layer 12 is preferably 5 μm or more, more preferably 10 μm or more, and particularly preferably 15 μm or more. The thickness of the polyethylene layer 12 is preferably 50 μm or less, more preferably 40 μm or less, and particularly preferably 30 μm or less.
[0039] The ratio R2 of the thickness of the high modulus layer to the total thickness of the polyethylene layer 12 is not particularly limited, but is preferably 50% or more, more preferably 65% or more, and particularly preferably 80% or more. By increasing R2, the contribution of the high modulus layer can be increased. Therefore, the multilayer film 10 can impart better bag-making suitability to the laminate. R2 may be 95% or less, or 90% or less.
[0040] When the outermost layer 11 is a non-stretched film, the polyethylene layer 12 is also preferably a non-stretched film. In this case, the adhesion between the outermost layer 11 and the polyethylene layer 12 is further improved, and peeling between the outermost layer 11 and the polyethylene layer 12 becomes less likely to occur. The polyethylene layer 12 may be in direct contact with the outermost layer 11 or may be in contact with the outermost layer 11 via an adhesive layer. When the polyethylene layer 12 is in direct contact with the outermost layer 11, it is preferable that the layer of the polyethylene layer 12 in contact with the outermost layer 11 is an adhesive resin layer.
[0041] <Laminate> Next, an embodiment of the laminate of the present disclosure will be described with reference to Fig. 2. Fig. 2 is a cross-sectional view showing one embodiment of the laminate of the present disclosure. 2, the laminate 100 includes a multilayer film 10 and a sealant layer 50. The sealant layer 50 contains a polyethylene resin. In the multilayer film 10, the polyethylene layer 12 is disposed on the sealant layer 50 side. The laminate 100 may further include a first adhesive layer 20 between the multilayer film 10 and the sealant layer 50. The laminate 100 may further include an intermediate layer 30 containing a polyethylene resin and a second adhesive layer 40, in this order, from the first adhesive layer 20 side between the first adhesive layer 20 and the sealant layer 50. The laminate 100 may further include a gas barrier layer (not shown). The laminate 100 may further include a printing layer. The laminate 100 can have excellent bag-making suitability and visibility.
[0042] The sealant layer 50, the intermediate layer 30, the gas barrier layer, the first adhesive layer 20, and the second adhesive layer 40 will be described in detail below.
[0043] (Sealant layer) The sealant layer 50 includes a polyethylene resin. Examples of polyethylene resins include low-density polyethylene resin (LDPE), medium-density polyethylene resin (MDPE), linear low-density polyethylene resin (LLDPE), very low-density polyethylene resin (VLDPE), ethylene-vinyl acetate copolymer (EVA), ethylene-α-olefin copolymer, ethylene-(meth)acrylic acid copolymer, etc. These can be used alone or in combination of two or more. From the viewpoint of environmental load, the polyethylene resin may be composed of a biomass-derived resin or a recycled resin.
[0044] The sealant layer 50 may further contain additives, such as a flame retardant, a slip agent, an antiblocking agent, an ultraviolet absorbing agent, an antioxidant, a plasticizer, a light stabilizer, a lubricant, a tackifier, and an antistatic agent, as necessary.
[0045] The sealant layer 50 preferably has a melting point lower than the melting point of the outermost layer 11 of the multilayer film 10. In this case, when the laminate 100 is heat-sealed, it is possible to heat-seal the sealant layer 50 while suppressing melting of the outermost layer 11.
[0046] The sealant layer 50 may be a stretched or unstretched film. The stretched film may be a uniaxially stretched film or a biaxially stretched film.
[0047] The thickness of the sealant layer 50 is not particularly limited and is appropriately adjusted depending on the application of the laminate 100. The thickness of the sealant layer 50 may be, for example, 10 μm or more, 25 μm or more, 30 μm or more, 40 μm or more, or 50 μm or more. The thickness of the sealant layer 50 may be 200 μm or less, 180 μm or less, 160 μm or less, 150 μm or less, 120 μm or less, or 100 μm or less.
[0048] (Middle class) The intermediate layer 30 contains a polyethylene-based resin. When the intermediate layer 30 contains a polyethylene-based resin, the mass proportion of the polyethylene-based resin in the entire laminate 100 can be made easier to increase. The intermediate layer 30 may or may not include a high elastic modulus layer having a composite elastic modulus of 1.4 GPa or more and less than 2.4 GPa, but preferably does. In this case, the density of the intermediate layer 30 is increased overall, and wrinkles are less likely to occur in the intermediate layer 30 when the intermediate layer 30 is subjected to processing such as vapor deposition, dry lamination, or printing, and the processing stability of the intermediate layer 30 is improved. In addition, the laminate 100 is more likely to maintain gas barrier properties even after heat sterilization treatment, and can have better heat resistance. The intermediate layer 30 may be a single layer or a multilayer. When the intermediate layer 30 is a multilayer, it may be composed of two outer layers and an inner layer disposed between the two outer layers, and the inner layer may be a single layer or a multilayer. It is preferable to adjust the composite modulus of the outer layer according to the required properties. Increasing the composite modulus can improve processability such as heat resistance and slipperiness, while decreasing the composite modulus can improve physical properties such as smoothness and transparency.
[0049] The intermediate layer 30 may further contain additives such as a flame retardant, a slip agent, an antiblocking agent, an ultraviolet absorber, an antioxidant, a plasticizer, a light stabilizer, a lubricant, a tackifier, and an antistatic agent, as necessary.
[0050] The intermediate layer 30 may be a stretched film or a non-stretched film. The stretched film may be a uniaxially stretched film or a biaxially stretched film.
[0051] The thickness of the intermediate layer 30 is not particularly limited, and can be appropriately determined according to the cost and application, taking into consideration the suitability of the manufacturing method and device, and the suitability for lamination with other layers. The thickness of the intermediate layer 30 is preferably 10 μm or more, more preferably 15 μm or more, and particularly preferably 20 μm or more. The thickness of the intermediate layer 30 is preferably 50 μm or less, more preferably 40 μm or less, and particularly preferably 30 μm or less.
[0052] (Gas barrier layer) The gas barrier layer may be disposed between the multilayer film 10 and the intermediate layer 30, or between the intermediate layer 30 and the sealant layer 50. The intermediate layer 30 may be provided inside the intermediate layer 30 as an organic gas barrier layer. Because the laminate 100 has a gas barrier layer, when a packaging bag is made using the laminate 100 and contents are placed in the packaging bag to produce a packaged product, deterioration of the contents due to gases such as water vapor and oxygen can be effectively suppressed. The gas barrier layer may include a vapor-deposited layer composed of an inorganic compound.
[0053] Examples of inorganic compounds constituting the vapor deposition layer include inorganic oxides such as aluminum oxide, silicon oxide, tin oxide, magnesium oxide, and mixtures thereof. From the viewpoint of more easily maintaining gas barrier properties and adhesion even after heat sterilization treatment, more excellent heat resistance, and visibility, the inorganic compound may contain at least one selected from the group consisting of aluminum oxide, silicon oxide, and magnesium oxide. When silicon oxide, for example, is used as the vapor deposition layer, the gas barrier layer becomes transparent, and therefore the visibility of the laminate 100 can be improved. The deposition layer can be formed by vacuum deposition of an inorganic compound such as silicon oxide or aluminum oxide, etc. The thickness of the deposition layer may be, for example, 15 to 30 nm. The gas barrier layer may be composed of only a vapor deposition layer, or may be composed of an anchor coat layer and a vapor deposition layer.
[0054] Although the gas barrier layer has gas barrier properties even when composed of only a vapor-deposited layer, it is preferable that the gas barrier layer is composed of a composite layer formed by further laminating a coating layer on the vapor-deposited layer.
[0055] When the gas barrier layer is composed of a composite layer, a reaction layer between the deposition layer and the coating layer occurs at the interface between the two layers, or the coating layer fills or reinforces defects or micropores such as pinholes, cracks, and grain boundaries that occur in the deposition layer, forming a dense structure. Therefore, a gas barrier layer composed of a composite layer combining a coating layer and a deposition layer realizes higher gas barrier properties, moisture resistance, and water resistance, and has flexibility that can withstand deformation due to external forces, thereby imparting suitability to the laminate 100 as a packaging material.
[0056] The coating layer can be formed, for example, by a coating method in which a coating agent is applied onto the vapor deposition layer and dried by heating. The coating agent can be based on an aqueous solution or a water / alcohol mixed aqueous solution containing at least one of a water-soluble polymer and one or more alkoxides, their hydrolysates, or tin chloride. The coating agent may further contain a silane monomer. In this case, the adhesion between the coating layer and the vapor deposition layer can be improved.
[0057] The anchor coat layer can be formed by a coating liquid containing a resin such as an acrylic resin, an epoxy resin, an acrylic urethane resin, a polyester polyurethane resin, or a polyether polyurethane resin. From the viewpoint of heat resistance and interlayer adhesive strength, the anchor coat layer may be formed by a coating liquid containing an acrylic urethane resin or a polyester polyurethane resin. The anchor coat layer can be formed by coating a coating liquid in which the resin is dissolved in a solvent using a coating method that applies a printing method such as gravure coating or a commonly known coating method.
[0058] (1st adhesive layer) An example of the first adhesive layer 20 is an adhesive layer formed using an adhesive.
[0059] Examples of the adhesive include known adhesives such as urethane adhesives, polyester adhesives, polyamide adhesives, epoxy adhesives, and isocyanate adhesives. From the viewpoint of environmental consideration, adhesives whose polymer components are derived from biomass or adhesives having biodegradability may be used. The adhesive may also be an adhesive having barrier properties.
[0060] The adhesive may be an adhesive containing an organic solvent or an adhesive not containing an organic solvent, but from the viewpoint of reducing the environmental load or reducing the amount of solvent remaining in the laminate, an adhesive not containing an organic solvent (a solvent-free adhesive) is preferable. Furthermore, compared with solvent-based adhesives, solvent-free adhesives generally can exhibit sufficient adhesive strength with a thin layer, and as a result, are suitable for improving the visibility of printed patterns.
[0061] The thickness of the first adhesive layer 20 is not particularly limited, and may be, for example, 1 μm or more, or 2 μm or more. By making the thickness of the first adhesive layer 20 2 μm or more, sufficient adhesive strength can be obtained. The thickness of the first adhesive layer 20 may be 50 μm or less, 5 μm or less, or 3 μm or less.
[0062] The first adhesive layer 20 is formed by coating using a conventional method such as direct gravure roll coating, gravure roll coating, kiss coating, reverse roll coating, Fontaine, and transfer roll coating, and exerts its effect by bonding it to another film (sealant layer 50) using a conventional method such as dry lamination or non-solvent lamination.
[0063] (Second adhesive layer) An example of the second adhesive layer 40 is an adhesive layer formed using an adhesive.
[0064] Examples of the adhesive include known adhesives such as urethane adhesives, polyester adhesives, polyamide adhesives, epoxy adhesives, and isocyanate adhesives. From the viewpoint of environmental consideration, adhesives whose polymer components are derived from biomass or adhesives having biodegradability may be used. The adhesive may also be an adhesive having barrier properties.
[0065] The adhesive may be an adhesive containing an organic solvent or an adhesive not containing an organic solvent, but from the viewpoint of reducing the environmental load or reducing the amount of solvent remaining in the laminate, it is preferable that the adhesive be an adhesive not containing an organic solvent (solvent-free adhesive).
[0066] The thickness of the second adhesive layer 40 is not particularly limited and may be, for example, 1 μm or more, or 2 μm or more. By setting the thickness of the second adhesive layer 40 to 2 μm or more, sufficient adhesive strength can be obtained. The thickness of the second adhesive layer 40 may be 50 μm or less, 5 μm or less, or 3 μm or less.
[0067] (Printing layer) The laminate 100 may include a printed layer as previously described. The printed layer may be provided on a surface of the polyethylene layer 12 of the multilayer film 10 or on at least one surface of the intermediate layer 30 . The print layer is provided at a position visible from the outside of the laminate 100 for the purposes of displaying information about the contents, identifying the contents, improving concealment, or improving the design of the packaging bag. The printing ink is not particularly limited, and is appropriately selected from known printing inks taking into consideration printability on other layers in the laminate 100, design such as color tone, adhesion, and safety as a food container. The printing method is not particularly limited and may be appropriately selected from known printing methods. Examples of printing methods that may be used include gravure printing, offset printing, gravure offset printing, flexographic printing, and inkjet printing. Among these, gravure printing is preferably used from the viewpoints of productivity and high definition of the pattern.
[0068] (Laminate) The mass ratio of the polyethylene resin in the entire laminate 100 is not particularly limited, but is preferably 90 mass% or more. By making the mass ratio of the polyethylene resin in the entire laminate 100 90 mass% or more, the laminate 100 can have better recyclability. The proportion of the polyethylene resin in the entire laminate 100 may be 92 mass % or more, 95 mass % or more, or 97 mass % or more.
[0069] When both the outermost layer 11 and the polyethylene layer 12 are non-stretched films, the sealant layer 50 is preferably also a non-stretched film. In this case, the sealant layer 50 has excellent adhesion and low-temperature sealability.
[0070] <Packaging products> Next, an embodiment of the packaging product of the present disclosure will be described with reference to Fig. 3. Fig. 3 is a cross-sectional view showing one embodiment of the packaging product of the present disclosure. As shown in Fig. 3, the packaged product 300 includes a packaging bag 200 and a content C accommodated in the packaging bag 200. The packaging bag 200 shown in Fig. 2 is obtained by making a bag from a pair of laminates 100. Specifically, the packaging bag 200 is obtained by using a pair of laminates 100 and heat-sealing the peripheral portions of the laminates 100 with the sealant layers 50 facing each other.
[0071] The packaging bag 200 is obtained by making the laminate 100 into a bag. The laminate 100 has excellent suitability for bag making, and therefore has an excellent appearance and excellent visibility. Therefore, the packaged product 300 also has an excellent appearance, and the contents C can be easily visually confirmed.
[0072] The packaging bag 200 can also be obtained by making a bag from one laminate 100. Specifically, the packaging bag 200 can also be obtained by folding one laminate 100 and heat-sealing the periphery of the laminate 100 with the sealant layers 50 facing each other.
[0073] The content C is not particularly limited, and examples of the content C include food, liquid, medicine, and electronic parts.
[0074] <Summary of this Disclosure> The outline of this disclosure is as follows. [1] A multilayer film comprising an outermost layer containing a thermoplastic resin and a polyethylene layer containing a polyethylene-based resin, wherein the thermoplastic resin has a melting point of 160°C or higher, and the polyethylene layer includes a high elastic modulus layer having a composite elastic modulus of 1.4 GPa or more and less than 2.4 GPa as measured by a nanoindentation method in a cross section in the thickness direction of the polyethylene layer. [2] The multilayer film described in [1], wherein the thickness of the high elastic modulus layer accounts for 50% or more of the total thickness of the polyethylene layer. [3] The multilayer film according to [1] or [2], wherein the thickness of the outermost layer accounts for 3% or more of the total thickness of the multilayer film. [4] The multilayer film described in any one of [1] to [3], wherein the degree of crystallinity of the polyethylene layer measured at a diffraction angle range of 10° to 30° by a parallel beam method of X-ray diffraction is less than 35%. [5] A multilayer film and a sealant layer are provided. the sealant layer comprises a polyethylene-based resin, The multilayer film is composed of the multilayer film according to any one of [1] to [4], A laminate, wherein the polyethylene layer is disposed on the sealant layer side of the multilayer film. [6] The laminate according to [5], wherein the mass proportion of the polyethylene resin in the laminate is 90 mass% or more. [7] The laminate described in [5] or [6], further comprising a first adhesive layer between the multilayer film and the sealant layer. [8] The laminate described in [7], further comprising an intermediate layer and a second adhesive layer, in that order, from the first adhesive layer side between the first adhesive layer and the sealant layer, wherein the intermediate layer contains a polyethylene-based resin. [9] The laminate described in [8], further comprising a gas barrier layer between the multilayer film and the intermediate layer.
[10] The laminate according to [8] or [9], further comprising a gas barrier layer between the intermediate layer and the sealant layer.
[11] A packaging bag obtained by forming the laminate according to any one of [5] to
[10] into a bag.
[12] A packaging product comprising the packaging bag described in
[11] and contents contained within the packaging bag. EXAMPLES
[0075] The present disclosure will be specifically described below with reference to examples, but the present disclosure is not limited to these examples.
[0076] <Resins Constituting the Multilayer Film and Intermediate Layer> The materials shown below were prepared as resins constituting the multilayer film and the intermediate layer.
[0077] PP: Polypropylene resin (density: 0.9g / cm 3 , MFR(190℃):0.8g / 10min, Melting point:160℃ PBT: Polybutylene terephthalate resin (density: 1.35g / cm 3 , melting point: 223℃) Ny: Polyamide resin (density: 1.13g / cm 3 , melting point: 220℃) EVOH: Ethylene vinyl alcohol copolymer (density: 1.19g / cm 3 , MFR(190℃):1.6g / 10min, Melting point:183℃ PET: Polyethylene terephthalate resin (density: 1.34g / cm 3 , melting point: 255℃) PE1: Maleic anhydride modified ethylene-propylene-butene-1 copolymer (density: 0.880 g / cm 3 , MFR(190℃):2.6g / 10min, composite elastic modulus:0.3GPa, melting point:90℃) PE2: Maleic anhydride modified linear low-density polyethylene (density: 0.910 g / cm3 , MFR(190℃):2.4g / 10min, composite elastic modulus:0.7GPa, melting point:120℃) PE3: High density polyethylene (density: 0.960g / cm 3 , MFR(190℃):0.85g / 10min, composite elastic modulus:2.1GPa, melting point:134℃) PE4: High density polyethylene (density: 0.963g / cm 3 , MFR(190℃):1.35g / 10min, composite elastic modulus:2.3GPa, melting point:139℃) PE5: High density polyethylene (density: 0.944g / cm 3 , composite elastic modulus: 1.7GPa, melting point: 131℃) PE6: Medium density polyethylene (density: 0.940g / cm 3 , MFR(190℃): 1.3g / 10min, composite elastic modulus: 1.5GPa, melting point: 129℃) PE7: Linear low-density polyethylene (density: 0.920 g / cm 3 , composite elastic modulus: 0.7GPa, melting point: 124℃) PE8: High density polyethylene (density: 0.960g / cm 3 , MFR (190℃): 1.0g / 10min, composite elastic modulus: 2.4GPa, melting point: 135℃)
[0078] Example 1 A multilayer film consisting of an outermost layer and a polyethylene (hereinafter also referred to as "PE") layer was produced by co-extrusion. PP was used as the resin for the outermost layer, PE1 was used as the resin for the adhesive resin constituting the PE layer, and PE3 was used as the resin for PE layer 1. Each was fed into an extruder to obtain a co-extruded multilayer film. At this time, the thicknesses of the outermost layer, adhesive resin layer, and PE layer 1 were as shown in Table 1. Next, a print layer displaying a predetermined pattern was printed on the PE layer of the multilayer film. A 60 μm-thick sealant layer made of LLDPE (melting point: 113° C., unstretched film) was attached to the surface of the print layer using a two-liquid adhesive (product name "Takelac A-525 / Takenate A-52", manufactured by Mitsui Chemicals, Inc.) to obtain a laminate.
[0079] Example 2 A laminate was obtained in the same manner as in Example 1, except that PBT was used as the outermost layer.
[0080] Example 3 A laminate was obtained in the same manner as in Example 1, except that Ny was used as the outermost layer and PE2 was used as the adhesive resin layer.
[0081] Example 4 A laminate was obtained in the same manner as in Example 1, except that EVOH was used as the outermost layer and PE2 was used as the adhesive resin layer.
[0082] Example 5 A laminate was obtained in the same manner as in Example 1, except that PET was used as the outermost layer.
[0083] Example 6 A laminate was obtained in the same manner as in Example 1, except that a mixture of Ny and PE3 (hereinafter also referred to as "Ny / PE3"; Ny:PE3 = 50:50 (mass ratio)) was used as the outermost layer, and PE2 was used as the adhesive resin layer.
[0084] Example 7 A laminate was obtained in the same manner as in Example 1, except that a mixture of PP and PE3 (hereinafter also referred to as "PP / PE3"; PP:PE3 = 50:50 (mass ratio)) was used as the outermost layer.
[0085] Example 8 A laminate was obtained in the same manner as in Example 1, except that PE4 was used as the PE layer 1.
[0086] Example 9 A laminate was obtained in the same manner as in Example 1, except that PE5 was used as the PE layer 1.
[0087] Example 10 A laminate was obtained in the same manner as in Example 1, except that the PE layer was configured as an adhesive resin layer made of PE1, a PE layer 1 made of PE3, a PE layer 2 made of PE7, and a PE layer 3 made of PE3. At this time, the thickness of each layer was as shown in Table 4.
[0088] Example 11 A laminate was obtained in the same manner as in Example 1, except that the PE layer was configured as an adhesive resin layer made of PE1, a PE layer 1 made of PE3, and a PE layer 2 made of PE6. At this time, the thickness of each layer was as shown in Table 4.
[0089] Example 12 A laminate was obtained in the same manner as in Example 1, except that the PE layer was configured as an adhesive resin layer made of PE1, a PE layer 1 made of PE6, a PE layer 2 made of PE3, and a PE layer 3 made of PE6. At this time, the thickness of each layer was as shown in Table 5.
[0090] (Example 13) A laminate was obtained in the same manner as in Example 1, except that a mixture of PE3 and PE7 (hereinafter also referred to as "PE3 / PE7"; PE3:PE7=70:30 (mass ratio)) was used as the PE layer 1.
[0091] (Examples 14 to 16) A multilayer film was obtained in the same manner as in Example 1, except that the thicknesses of the outermost layer, adhesive resin layer, and PE layer 1 were as shown in Tables 6 and 7. Next, as a film for intermediate layer, an intermediate layer 1 made of PE6, an intermediate layer 2 made of PE3, and an intermediate layer 3 made of PE6 were laminated by a co-extrusion method so as to have thicknesses of 5 μm, 15 μm, and 5 μm, respectively, to produce a PE film with an overall thickness of 25 μm. The PE layer of the multilayer film and the intermediate layer 1 of the film for intermediate layer were bonded together using a two-liquid adhesive (product name "Takelac A-525 / Takenate A-52", manufactured by Mitsui Chemicals, Inc.). Furthermore, the intermediate layer 3 of the film for intermediate layer and the sealant layer were similarly bonded together to obtain a laminate.
[0092] (Example 17) Except for setting the thicknesses of the outermost layer, adhesive resin layer and PE layer 1 as shown in Table 7 and obtaining a multilayer film in the same manner as in Example 3, laminates were obtained in the same manner as in Examples 14 to 16.
[0093] (Example 18) A laminate was obtained in the same manner as in Example 1, except that the adhesive used was a product named "TSN-4864A / TSN-4864B3" (manufactured by Toyo-Morton Co., Ltd.). At this time, the adhesive was applied in a coating amount of about 2 g / m2. 2 The surface of the printed layer was coated with the adhesive so that the adhesive became uniform, and the layer was then laminated with a sealant layer made of LLDPE.
[0094] (Example 19) The coextruded multilayer film was further stretched three times in each of the MD and TD directions to perform a biaxial stretching process, adjusting the thicknesses of the outermost layer, adhesive resin layer and PE layer 1 as shown in Table 8, and a laminate was obtained in the same manner as in Example 1, except that a printing layer was printed on this multilayer film.
[0095] (Example 20) The coextruded multilayer film was further stretched 4 times in each of the MD and TD directions to perform a biaxial stretching process, adjusting the thicknesses of the outermost layer, adhesive resin layer and PE layer 1 as shown in Table 9, and a laminate was obtained in the same manner as in Example 1, except that a printing layer was printed on this multilayer film.
[0096] Example 21 The coextruded multilayer film was further stretched 5 times in each of the MD and TD directions to perform a biaxial stretching process, adjusting the thicknesses of the outermost layer, adhesive resin layer and PE layer 1 as shown in Table 9, and a laminate was obtained in the same manner as in Example 1, except that a printing layer was printed on this multilayer film.
[0097] Comparative Example 1 A laminate was obtained in the same manner as in Example 1, except that PE3 was used as the outermost layer, and as the PE layers, a PE layer 1 made of PE7 and a PE layer 2 made of PE3 were used.
[0098] Comparative Example 2 A laminate was obtained in the same manner as in Example 1, except that PE7 was used as the PE layer 1.
[0099] Comparative Example 3 A laminate was obtained in the same manner as in Example 1, except that PE8 was used as the PE layer 1.
[0100] Comparative Example 4 The coextruded multilayer film was further stretched 7 times in each of the MD and TD directions to perform a biaxial stretching process, adjusting the thicknesses of the outermost layer, adhesive resin layer and PE layer 1 as shown in Table 11, and a laminate was obtained in the same manner as in Example 1, except that a printing layer was printed on this multilayer film.
[0101] <Composite Elastic Modulus> (Preparation of measurement samples) Samples for measuring the composite elastic modulus of the PE layer and the intermediate layer in the cross section of the laminates obtained in the Examples and Comparative Examples were prepared by the following procedure. First, the laminate including the PE layer and the intermediate layer was cut into a rectangular or wedge shape with a razor, and the cut pieces were embedded in embedding resin. Toa Gosei's D-800 photocurable resin was used as the embedding resin, and the embedding resin of the cut pieces was hardened by light irradiation after embedding to obtain a hardened body. The hardened body was fixed with an insert for an AFM sample holder, trimmed with a glass knife at room temperature (25°C) and the cross-section of the film was cut, and the cross-section was cut with a diamond knife at a cutting speed of 1.0 mm / sec and a cutting film thickness of 200 nm until a mirror surface was obtained. In this way, a sample was obtained. Leica's ultramicrotome EMUC7 was used as the cross-section cutting device. The cutting direction was parallel to the layer interface.
[0102] (Measurement of composite elastic modulus) The composite elastic modulus of the PE layer and the intermediate layer represents the composite elastic modulus calculated by the nanoindentation method. The nanoindentation method is a measurement method in which a quasi-static indentation test is performed on a target object to be measured to obtain the mechanical properties of the sample. The measurement device used was a Hysitron TI-Premier (product name) manufactured by Bruker Japan Co., Ltd. The indenter used was a Berkovich-type diamond indenter manufactured by Bruker Japan Co., Ltd. The measurement by the nanoindentation method was performed as follows. First, the diamond indenter was scanned on the cross section of the sample to obtain a shape image of the sample, and the measurement position on the sample was specified. Then, the diamond indenter was indented to a depth of 80 nm at a pressing speed of 80 nm / sec in the displacement control mode at room temperature (25°C), and the maximum depth was held for 1 second, and then the load was removed at a speed of 80 nm / sec. Then, the unloading curve in the 60-95% range of the maximum load at the time of unloading was analyzed by the Oliver-Pharr method, and the stiffness (stiffness at the maximum indentation depth) indicating the ratio of the change in load to the displacement and the contact projected area (the projected area of the part where the indenter and the sample are in contact at the maximum load) were obtained, and the composite elastic modulus was calculated based on these stiffness and contact projected area. At this time, a test was conducted in advance on fused quartz as a standard sample, and the relationship between the contact depth between the indenter and the sample and the contact projected area was calibrated. The results of the composite elastic modulus are shown in Tables 1 to 11.
[0103] <Evaluation> (1) Heat seal temperature Two samples measuring 60 mm wide and 50 mm long were cut from the laminates obtained in the Examples and Comparative Examples, and the two samples were overlapped with the sealant layers facing each other, and heat-sealed using a seal bar under the following conditions to obtain a fused product. A total of three measurement samples A measuring 15 mm wide were taken from the obtained fused product. (Sealing conditions) Seal bar width: 10mm Sealing time: 1s Sealing pressure: 0.2MPa Sealing temperature: 80℃ For each of the three measurement samples A thus prepared, a peel test was performed in accordance with JIS Z1707:2019 "Heat seal strength test", in which the two samples were peeled off at a test speed of 300 mm / min. Next, a test specimen A was prepared in the same manner as above, except that the sealing temperature was increased by 10°C, and a peel test was performed in the same manner as above. Thereafter, the above operations were repeated. Then, during the peel test of the test specimen A, if peeling did not occur between the sealant layers but occurred between the PE layer and the sealant layer, or if the test specimen A broke, the measurement was terminated, and the average value of the seal temperatures of the three test specimens A that had been subjected to the peel test immediately before that test specimen A was taken as the "heat seal temperature." The results are shown in Tables 1 to 11.
[0104] (2) Bag making suitability The laminates obtained in the Examples and Comparative Examples were evaluated for suitability for bag making as follows.
[0105] (2-1) Appearance evaluation of the seal First, for the laminates obtained in the examples and comparative examples, the appearance of the seal portion was evaluated as follows. That is, two samples of 60 mm width × 50 mm length were cut from the laminates obtained in the Examples and Comparative Examples, and the two samples were overlapped with the sealant layers facing each other, and heat-sealed using a seal bar under the following conditions to obtain a fused body. A total of three measurement samples B of 15 mm width were taken from the obtained fused body. (Sealing conditions) Seal bar width: 10mm Sealing time: 1s Sealing pressure: 0.2MPa Sealing temperature: 80℃ The appearance of the sealed portion of each of the three measurement samples B thus prepared was visually observed to check for any abnormalities in appearance, such as the sealed portion sticking to the seal bar, wrinkles, air bubbles, whitening, shrinkage or breakage. Next, measurement sample B was prepared in the same manner as above, except that the sealing temperature was increased by 5° C., and the appearance of the sealed portion was observed in the same manner as above. Thereafter, the appearance of the sealed portion was repeatedly observed until a measurement sample B with an abnormal appearance was found. The highest sealing temperature among the sealing temperatures of the measurement sample B at which no abnormality in appearance occurred was determined as the “maximum temperature T1 (° C.).” The results are shown in Tables 1 to 11.
[0106] (2-2) Evaluation of outermost layer adhesion First, for the laminates obtained in the Examples and Comparative Examples, the adhesion of the outermost layer was evaluated as follows. That is, two samples measuring 60 mm wide x 50 mm long were cut from the laminates obtained in the Examples and Comparative Examples, the two samples were overlapped with the outermost layers facing each other, and this was sandwiched between two PET films (product name "P60", Toray Industries, Inc., 12 μm) and heat sealed under the following conditions using a seal bar. A total of three measurement samples C measuring 15 mm wide were taken from the obtained samples and used for the measurement. (Sealing conditions) Seal bar width: 10mm Sealing time: 1s Sealing pressure: 0.2MPa Sealing temperature: 110℃ For the measurement sample C thus prepared, in accordance with JIS Z1707:2019 "Heat seal strength test," the two samples were peeled off at a test speed of 300 mm / min, and the heat seal strength between the outermost layers was measured. Next, measurement sample C was prepared in the same manner as above, except that the sealing temperature was increased by 5° C., and the heat seal strength between the outermost layers was measured in the same manner as above. Thereafter, the heat seal strength between the outermost layers was repeatedly measured until the heat seal strength of measurement sample C became 1 N / 15 mm or more. The highest sealing temperature among the sealing temperatures at which the heat seal strength between the outermost layers became less than 1 N / 15 mm was defined as the “maximum temperature T2 (° C.).” The results are shown in Tables 1 to 11.
[0107] (2-3) Evaluation The difference ΔT (=TL-T0) between the lower temperature TL (°C) of the maximum temperatures T1 and T2 and the heat sealing temperature T0 (°C) was calculated. The results are shown in Tables 1 to 11. ΔT indicates the allowable range of heat sealing. The bag-making suitability of the laminate was then evaluated based on the following evaluation criteria. The results are shown in Tables 1 to 11. (Evaluation Criteria) ◎: ΔT is 30℃ or higher ○: ΔT is between 20℃ and 30℃ ×: ΔT is less than 20℃ A laminate rated as "◎" is unlikely to cause bag-making defects even if the heat-sealing temperature T0 varies, and the possibility that bag making will become impossible is very low, indicating that the suitability for bag making is very good. A laminate rated as "◯" is likely to cause bag making defects if the heat-sealing temperature T0 varies, but the possibility that bag making will become impossible is low, indicating that the suitability for bag making is good. A laminate rated as "×" is unlikely to cause bag making, and the suitability for bag making is not good.
[0108] (3) Visibility For the laminates obtained in the Examples and Comparative Examples, the pattern displayed by the printed layer was visually observed from the outermost layer side, and the visibility was evaluated based on the following evaluation criteria. (Evaluation Criteria) ◯: The pattern displayed by the printing layer was clearly visible. ×: The pattern displayed by the print layer was blurred and unclear.
[0109] (4) Laminate strength Three strip-shaped test pieces with a width of 15 mm were taken from the laminates obtained in the examples and comparative examples. The multilayer film layer was peeled from the sealant layer or intermediate layer, and the laminate strength was measured in accordance with JIS Z1707. The laminate strength was measured by 90° peeling (normal 90° peeling) and 180° peeling (normal 180° peeling), and the adhesion was evaluated based on the following evaluation criteria. In the following evaluation criteria, "laminate strength" refers to the smaller laminate strength between the laminate strength measured at 90° peeling and the laminate strength measured at 180° peeling, and when the laminate strength measured at 90° peeling and the laminate strength measured at 180° peeling are the same laminate strength, the laminate strength is referred to. (Evaluation Criteria) ◎: Lamination strength is 5N / 15mm or more 〇: Laminate strength is 2N / 15mm or more and less than 5N / 15mm ×: Lamination strength is less than 2N / 15mm
[0110] [Table 1] [Table 2] [Table 3] [Table 4] [Table 5] [Table 6] [Table 7] [Table 8] [Table 9] [Table 10] [Table 11]
[0111] The results shown in Tables 1 to 11 demonstrate that all of the laminates of the examples have excellent suitability for bag formation and also have excellent visibility. On the other hand, it was found that the laminates of the comparative examples did not have good suitability for bag making or good visibility. In the appearance evaluation of the laminates of the comparative examples 1 and 2, the film stuck to the seal bar in the area where the heat sealing temperature was relatively low, and in the laminates of the comparative example 4, the film contracted in the area where the heat sealing temperature was relatively low, resulting in poor appearance. Therefore, it was confirmed that the multilayer film of the present disclosure can impart excellent bag-making suitability to the laminate and can provide excellent visibility. [Explanation of symbols]
[0112] Reference Signs List 10...multilayer film, 11...outermost layer, 12...polyethylene layer, 20...first adhesive layer, 30...middle layer, 40...second adhesive layer, 50...sealant layer, 100...laminate, 200...packaging bag, 300...packaged product, C...contents.
Claims
1. An outermost layer containing a thermoplastic resin; A multilayer film comprising a polyethylene layer containing a polyethylene-based resin, The thermoplastic resin has a melting point of 160° C. or more, A multilayer film, wherein the polyethylene layer includes a high elastic modulus layer having a composite elastic modulus of 1.4 GPa or more and less than 2.4 GPa as measured by a nanoindentation method in a cross section in the thickness direction of the polyethylene layer.
2. 2. The multilayer film according to claim 1, wherein the thickness of said high modulus layer accounts for 50% or more of the total thickness of said polyethylene layers.
3. 2. The multilayer film according to claim 1, wherein the ratio of the thickness of the outermost layer to the total thickness of the multilayer film is 3% or more.
4. The multilayer film according to any one of claims 1 to 3, wherein the degree of crystallinity of the polyethylene layer is less than 35% as measured by a parallel beam method of X-ray diffraction in the diffraction angle range of 10° to 30°.
5. A multilayer film and a sealant layer are provided, the sealant layer comprises a polyethylene-based resin, The multilayer film is composed of the multilayer film according to claim 1, A laminate, wherein the polyethylene layer is disposed on the sealant layer side of the multilayer film.
6. The laminate according to claim 5 , wherein the mass ratio of the polyethylene resin in the entire laminate is 90 mass % or more.
7. 6. The laminate of claim 5, further comprising a first adhesive layer between the multilayer film and the sealant layer.
8. An intermediate layer and a second adhesive layer are further provided between the first adhesive layer and the sealant layer, in this order from the first adhesive layer side, The laminate according to claim 7 , wherein the intermediate layer comprises a polyethylene-based resin.
9. The laminate according to claim 8 , further comprising a gas barrier layer between the multilayer film and the intermediate layer.
10. The laminate of claim 8 , further comprising a gas barrier layer between the intermediate layer and the sealant layer.
11. A packaging bag obtained by producing the laminate according to any one of claims 5 to 10.
12. A packaging product comprising the packaging bag of claim 11 and contents contained within the packaging bag.
Citation Information
Patent Citations
Layered product, packaging material, and packaging bag
WO2022230812A1